RUWAYS OF IMPROVEMENT OF QUALITY OF GRANTING OF EDUCATIONAL SERVICES FOR PERSONS WITH DISABILITIES - Еlena A Khudorenko (Статистика и экономика)
The article discusses the features of educational services for persons with disabilities, studied the stages of educational services to the Russian people with disabilities. The author examines the factors affecting the quality of each of the stages, and proposes ways to improve them.